Epistemological vulnerabilities of current psychiatry and global mental health: a critical approach from Latin America - Alarcón-Guzmán, Renato (2024)
In recognition of the great advance of psychiatry as a medical specialty, and of the global mental health movement in the clinical management of mental health problems and disorders, it is extremely important to explore the conceptual dilemmas, structural limitations, and epistemological tensions in search of clearer, broader, deeper and more consistent approaches to both the theory and practice of psychiatry. The analysis pursued in this study examines predominant paradigms, and substantiates proposals such as the inclusion of socio-cultural concepts in the diagnosis beyond its exclusive basis on manuals, the elimination of a circular etio-pathogenic thinking, the dogmatic declarations of an “evidence-based medicine”, the pretended neutrality of science, and the idealized polarization of mental health and mental illness; at the same time, the clear utility of sociocultural concepts and epistemological perspectives in the understanding of every type of psychopathological events, is reaffirmed. These critical approaches attempt to amplify psychiatry’s ontological horizons and liberate it from entrapments imposed by different levels and measures of power-based relationships. The article attempts to establish a continuity with the critical reflections about the growth of Global Mental Health elaborated and shared by Duncan Pedersen and other scholars from the Americas, oriented to the revalorization of thoughts and actions of a mental health better adapted to the community-based and socio-cultural needs of Latin America in particular.